Advantages of Combining Different Processes for Diesel Fuel Desulfurization; Petroleum and Coal; Vol. 65, iss. 1 - Baklashkina K. A. Kseniya Andreevna; Samborskaya M. A. Marina Anatolievna; Kraevskaya I. O. Irina Olegovna; Krivtsova K. B. Kseniya Borisovna (2023, 2023)
Title screen